Comparative urban research from theory to practice : co-production for sustainability - Simon, David; Palmer, Henrietta; Riise, jan (Bristol University Press, 2020)
Available Open Access under CC-BY-NC license. Reports on the innovative, transdisciplinary co-production on sustainable urbanisation being undertaken by Mistra Urban Futures, a highly influential research centre based in Sweden, this book makes a significant contribution to evolving theory about comparative urban research.